Modified Boltzmann Factor on Rupture Probability - rizal kurniadi (Institut Teknologi Bandung, 2022)
Fission Products are data that is very much needed for developing nuclear technology. Considering that the experimental results of nuclear data are minimal, theoretical modeling and calculations are needed. One of the theoretical models is the